Hormonal Changes in the Uterus During Pregnancy - Lessons from the Ewe: A Review - Rahman, Abu Nasar Md. Aminoor (Journal of Agriculture & Rural Development, 2008)
Pregnancy is the main event in the life of a female mammal to reproduce its progeny and maintain the integrity of the species. It is a very coordinated process involving reproductive organs and changes in the tissue concentration of various hormones, cytokines, enzymes and growth factors, of which hormones are most important. Various hormones are involved in the preparation of the uterus of ewe for conception of embryo, growth and development of embryo and foetus, maintenance of pregnancy and birth of a healthy lamb. However, pregnancy mainly involved two hormones, namely progesterone and oestrogens. Other hormones involved in this process are prostaglandin, cortisone, relaxin and oxytocin, which are mainly important for parturition. The endocrine changes in the ewe during the oestrous cycle, pregnancy and parturition dramatically affect the structure of the endometrium as well as the uterine immune system. During the 17-day oestrus cycle, progesterone dominates for about 13 days and oestrogens dominate for 3-4 days. In the pregnant ewe, oestogens are necessary for the growth and development of the ovarian follicles. However, once the ewe become pregnant progesterone become the key hormone to maintain the pregnancy and, therefore, known as pregnancy hormone. Progesterone dominates until the onset of parturition when endometrium switches from a progesterone-dominated state to an oestrogen-dominated state. Therefore, this paper reviews the hormonal profiles and endocrinological changes that occur during oestrous cycle and different stages of pregnancy in the ewe. The paper also illustrates the important immunological changes of the uterus that occur with the endocrinological changes. Key words: Oestrous cycle, pregnancy, parturition, endometrium, immune cells, ewe.